2009
DOI: 10.1007/s00421-009-1172-9
|View full text |Cite
|
Sign up to set email alerts
|

Energy systems contributions in 2,000 m race simulation: a comparison among rowing ergometers and water

Abstract: This study investigated the energy system contributions of rowers in three different conditions: rowing on an ergometer without and with the slide and rowing in the water. For this purpose, eight rowers were submitted to 2,000 m race simulations in each of the situations defined above. The fractions of the aerobic (W (AER)), anaerobic alactic (W (PCR)) and anaerobic lactic (W ([La-])) systems were calculated based on the oxygen uptake, the fast component of excess post-exercise oxygen uptake and changes in net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 15 publications
6
48
0
3
Order By: Relevance
“…26 The TE for mean power recorded from trials 1 to 2 (1.8%), 2 to 3 (2.9%), and overall (2.4%) indicates good reproducibility across repeated trials, which concurs with our experimental hypothesis. TE was similar to that reported by Schabort et al 4 28,29 ; however, the participants in the current study had a higher body mass, so larger absolute VO 2 values would be expected.…”
Section: Discussionsupporting
confidence: 89%
“…26 The TE for mean power recorded from trials 1 to 2 (1.8%), 2 to 3 (2.9%), and overall (2.4%) indicates good reproducibility across repeated trials, which concurs with our experimental hypothesis. TE was similar to that reported by Schabort et al 4 28,29 ; however, the participants in the current study had a higher body mass, so larger absolute VO 2 values would be expected.…”
Section: Discussionsupporting
confidence: 89%
“…WPCR 시스 템은 10초 스프린트 테스트 후 초과산소 섭취량(EPOCFAST)을 고려하 여 산출되었으며, off VO2의 단일 및 이중 지수모델(mono-and bi-exponential models)에 맞춰 분석되었다. 이중 지수모델의 느린 구성 요소 (slow component)는 무시되었으며 단일 지수모델의 빠른 구성 요소(fast component)가 WPCR 의 분석에 쓰였다[14][15][16][17]23]. WLa -시스템 분석은 1 mmol·L -1 혈중 젖산 축적의 동등 값인 체질양의 3 ml O2 kg -1 을 사용하 였다[24].…”
unclassified
“…In elite rowers the physiological determinants of aerobic performance such as maximal oxygen uptake (VO 2 max), lactate and ventilatory thresholds reach high values during exertion [2][3][4]. recent data have indicated that during a competitive 2-km distance aerobic energy is responsible for about 87% of total energy demands [5]. In addition, a close correlation has been found between rowing performance and VO 2 max [6].…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, isokinetic and isometric knee extension strength and power during simulated rowing exercises are also correlated with ergometric rowing performance [9,10]. recently anaerobic energy sources were found to provide 13% of total energy demands during on-water 2000 m rowing with similar contribution to the lactic and alactic pathways (6 % and 7%, respectively) [5].…”
Section: Introductionmentioning
confidence: 99%